Assessment On The Effect Of Health Teaching Regarding Vitamin A Deficiency In Children On Knowledge Of Mothers Residing In Selected Areas (Journal of Pharmaceutical Negative Results, 2022)
Child is precious and beautiful a source of joy and happiness a focus of love and care a subject of dreams of the future‖ .The physical health of a child is essential because it is associated with the mental and social development of children. Mothers are the first care providers of their children. One of the ways to achieve reduction of under-five mortality is to educate the mothers on matters pertaining to child care Aim of the study .-A study was conducted to Assess the effect of health teaching regarding Vitamin A deficiency in children on knowledge of mothers residing in selected areas. Methodology- The main study was conducted from 21st March to 30th April in Santh tukaram nagar, Mahesh nagar, Mukesh nagar and yeshwanth nagae, Pimpri, pune. The samples included 60 mothers with under-five children. Data was analyzed by using descriptive and inferential statistics. Result- Paired t-test was used for the comparison of the knowledge gain in the pre test and post test among mothers regarding assessment on the effect of health teaching regarding Vitamin A deficiency in children on knowledge of mothers 8.3, whereas post test mean score was 16.7. Tvalue was 20.6. Corresponding p- value was 0.000, which is small (less than 0.050, hence the null hypothesis is rejected. Hence, from the scores obtained in pre test and post test the knowledge scores, it is evident that the knowledge score in pre test is significantly high as compared to the post test. This showed that health teaching was found to be highly beneficial in improving the knowledge of mothers regarding assessment on the effect of health teaching regarding Vitamin A deficiency in children Conclusion -The result of the present study shows that there was significant difference in the pre-test and post test knowledge score of mothers. Hence, this indicates that the health teaching is an effective tool in increasing the knowledge of the mothers with under-five children.